Tegami bachi letter bee. Volume 15, To the little people - Asada, Hiroyuki, 1968- (Viz Media, 2013)
"Searching for the truth about Amberground, Lag heads home to the little town of Campbell. There, a woman named Sabrina Mary holds the secrets he seeks. But can he handle what he learns about his world, his government-- and his own mother?" -- from publisher's web site.